Transcription Profiling of Cultured Acropora digitifera Adult Cells Reveals the Existence of Ancestral Genome Regulatory Modules Underlying Pluripotency and Cell Differentiation in Cnidaria. (27th January 2021) - Reyes-Bermudez, Alejandro; Hidaka, Michio; Mikheyev, Alexander
Abstract: Due to their pluripotent nature and unlimited cell renewal, stem cells have been proposed as an ideal material for establishing long-term cnidarian cell cultures. However, the lack of unifying principles associated with "stemness" across the phylum complicates stem cells' identification and isolation. Here, we for the first time report gene expression profiles for cultured coral cells, focusing on regulatory gene networks underlying pluripotency and differentiation. Cultures were initiated from Acropora digitifera tip fragments, the fastest growing tissue in Acropora . Overall, in vitro transcription resembled early larvae, overexpressing orthologs of premetazoan and Hydra stem cell markers, and transcripts with roles in cell division, migration, and differentiation. Our results suggest the presence of pluripotent cell types in cultures and indicate the existence of ancestral genome regulatory modules underlying pluripotency and cell differentiation in cnidaria. Cultured cells appear to be synthesizing protein, differentiating, and proliferating.